2004
DOI: 10.1111/j.1365-2133.2004.06203.x
|View full text |Cite
|
Sign up to set email alerts
|

Ovariectomy is sufficient to accelerate spontaneous skin ageing and to stimulate ultraviolet irradiation-induced photoageing of murine skin

Abstract: These results suggest that ovariectomy alone is sufficient to accelerate skin ageing and to increase UV sensitivity, which results in the further deterioration of the skin and photoageing, and may account for the accelerated skin ageing seen in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
68
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 26 publications
5
68
1
2
Order By: Relevance
“…1,6,7) Inhibition of the UVB-induced increase in skin elastase activity prevented by the agent maintained the linearity of dermal elastic fibers and inhibited the decrease in skin elasticity, resulting in the inhibition of wrinkle formation. 1,6,7) This finding suggested that application of an elastase inhibitor immediately after UVB exposure would inhibit photoaging of the skin, mainly wrinkles.It has been shown that chronic UVB irradiation of the dorsal skin forms wrinkles in hairless mice 8,9) and that chronic ultraviolet-A (UVA) irradiation forms mainly sags. 8,9) In animal models, chronic UVA irradiation increased skin elastase activity and destroyed the 3-dimensional structure of dermal elastic fibers, decreasing skin elasticity, similarly to UVB irradiation.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…1,6,7) Inhibition of the UVB-induced increase in skin elastase activity prevented by the agent maintained the linearity of dermal elastic fibers and inhibited the decrease in skin elasticity, resulting in the inhibition of wrinkle formation. 1,6,7) This finding suggested that application of an elastase inhibitor immediately after UVB exposure would inhibit photoaging of the skin, mainly wrinkles.It has been shown that chronic UVB irradiation of the dorsal skin forms wrinkles in hairless mice 8,9) and that chronic ultraviolet-A (UVA) irradiation forms mainly sags. 8,9) In animal models, chronic UVA irradiation increased skin elastase activity and destroyed the 3-dimensional structure of dermal elastic fibers, decreasing skin elasticity, similarly to UVB irradiation.…”
mentioning
confidence: 99%
“…It has been shown that chronic UVB irradiation of the dorsal skin forms wrinkles in hairless mice 8,9) and that chronic ultraviolet-A (UVA) irradiation forms mainly sags. 8,9) In animal models, chronic UVA irradiation increased skin elastase activity and destroyed the 3-dimensional structure of dermal elastic fibers, decreasing skin elasticity, similarly to UVB irradiation.…”
mentioning
confidence: 99%
See 3 more Smart Citations